Reciprocal Data Portability to Foster Financial Services Competition in the Open Banking System Era - Wiwoho, Jamal; Pati, Umi Khaerah; Pratama, Anugrah Muhtarom (Yustisia, 2024)
This article analyzes the feasibility of incorporating reciprocal financial data into Indonesia's open banking system by studying its implementation in the United Kingdom and other countries. The methodology employed is conceptual, statutory, and comparative legal, utilizing data gathered from secondary legal sources. The study discovered that reciprocal data finance could be a supplementary measure to enhance data portability rights. This approach enables banks to provide compensation for access to account data, utilizing the concept of "paying by data". Indonesia should contemplate the adoption of data reciprocity alongside the portability rights outlined in Article 13 of the PDP Law. Subsequently, it can be configured inside the SNAP settings. Before proceeding with this development, it is crucial to establish Open banking in Indonesia by effectively balancing the goals of personal data rights and market competition. This circumstance will encourage Bank Indonesia to collaborate with other regulatory bodies, such as competition authorities, data protection regulators, and sector regulators. Despite potential differences in their objectives, this collaboration is necessary as reciprocal data portability initiatives may involve multiple regulatory domains.